Introducing Precision Medicine into an Undergraduate Medical Curriculum: An Interactive Lecture and Case-Based Learning Activity - Mara Rao; Christin Traba; Joshua Kra; Malcolm D. Mattes (Journal of Cancer Education, 2026)
Precision Medicine (PM)–the use of genomic, environment, and lifestyle data to design care based on individual patient characteristics–has become increasingly important in oncology practice. However, many medical schools lack dedicated instruction in this area. This study aimed to develop a novel educational session integrating PM into the Rutgers New Jersey Medical School third-year curriculum. An in-person, 1.5-h session was implemented, consisting of a lecture introducing definitions, diagnostic and therapeutic platforms, and challenges in PM, followed by an interactive clinical case discussing its applications in non-small cell lung cancer. Pre- and post-assessments evaluated students’ perceived abilities and attitudes and their knowledge and application of PM concepts. The session was attended by 178 students, with 136 paired pre- and post-tests available for analysis (pre-test response rate 92%, post-test 78%). After the session, students believed that they had a greater ability to apply PM in clinical scenarios (pre-test mean 2.7/5, post-test mean 4.3/5, p < 0.01) and perceived greater importance of learning about PM (pre-test mean 3.7/5, post-test mean 4.4/5, p < 0.01). Responses also showed modest improvement in objective content scores (pre-test mean 2.9/10, post-test mean 4.8/10, p < 0.01). At the end of the session, over 90% of students reported that they planned to apply what they had learned in their future practice of medicine. Overall, the session was effective in increasing participants’ understanding, confidence, and appreciation of PM. Future efforts should explore broader integration of PM content into curricula to better prepare students for its growing role in clinical practice.